2012
DOI: 10.1104/pp.112.205922
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of miR399f Transcription by AtMYB2 Affects Phosphate Starvation Responses in Arabidopsis  

Abstract: Although a role for microRNA399 (miR399) in plant responses to phosphate (Pi) starvation has been indicated, the regulatory mechanism underlying miR399 gene expression is not clear. Here, we report that AtMYB2 functions as a direct transcriptional activator for miR399 in Arabidopsis (Arabidopsis thaliana) Pi starvation signaling. Compared with untransformed control plants, transgenic plants constitutively overexpressing AtMYB2 showed increased miR399f expression and tissue Pi contents under high Pi growth and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
101
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(106 citation statements)
references
References 53 publications
3
101
2
Order By: Relevance
“…Under P deficiency, Arabidopsis phr1 mutants showed significantly reduced expressions of miR399 as well as group of other P related genes, while set of P deficiency-responsive genes were found upregulated in pho2 mutants under sufficient P availability, hence, concluded that PHR1 functions upstream of miR399 and PHO2, however, it is not the only element required for miR399 induction in P signaling network (Bari et al, 2006). Another recent report conducted by Baek et al (2013), demonstrated that miR399f belongs to Arabidopsis, transcriptionally regulated by MYB TF induced in P-deprived plants thereby binding to a MYB binding-site present in the promoter region of miR399f. Previous compelling evidences demonstrated that miR399 act as positive regulator under P deficiency, while PHO2; a target gene for miR399, behave as negative regulator and inhibit P uptake under normal P concentrations (Lin et al, 2008;Yuan and Liu, 2008).…”
Section: Mirnas and Their Targets Under Limited Phosphorousmentioning
confidence: 99%
“…Under P deficiency, Arabidopsis phr1 mutants showed significantly reduced expressions of miR399 as well as group of other P related genes, while set of P deficiency-responsive genes were found upregulated in pho2 mutants under sufficient P availability, hence, concluded that PHR1 functions upstream of miR399 and PHO2, however, it is not the only element required for miR399 induction in P signaling network (Bari et al, 2006). Another recent report conducted by Baek et al (2013), demonstrated that miR399f belongs to Arabidopsis, transcriptionally regulated by MYB TF induced in P-deprived plants thereby binding to a MYB binding-site present in the promoter region of miR399f. Previous compelling evidences demonstrated that miR399 act as positive regulator under P deficiency, while PHO2; a target gene for miR399, behave as negative regulator and inhibit P uptake under normal P concentrations (Lin et al, 2008;Yuan and Liu, 2008).…”
Section: Mirnas and Their Targets Under Limited Phosphorousmentioning
confidence: 99%
“…All miR399 genes present in Arabidopsis harbor PHR1-binding site P1BS in their promoters (Bari et al 2006 ). Also several other P-responsive cis -regulatory elements were identifi ed in the promoters of these phosphate-responsive miRNAs including PHO, PHO-like, W-box, NIT2, and MYB-binding sites (Zeng et al 2010 ;Xu et al 2013 ;Baek et al 2013 ). Further fi ndings also indicated that miR399-mediated regulation of PHO2 is under the control of target mimicry.…”
Section: Phosphate Homeostasismentioning
confidence: 92%
“…Several abiotic stress-associated transcription factorbinding motifs are identifi ed in the regulatory region of stress-responsive miRNAs in rice (Devi et al 2013 ) and in Arabidopsis (Megraw et al 2006 ). Several individual miRNA studies also identifi ed the cis -acting elements in their upstream region, e.g., ABA-mediated response of AtMIR168a is due to the presence of two ABRE in upstream region (Li et al 2012a ), the presence of PHR1-binding site and other phosphate-responsive cis regulatory elements in the promoter of phosphateresponsive miRNAs (Bari et al 2006, Zeng et al 2010, Baek et al 2013 ) and core GTAC motif as AtSPL7-binding site in the upstream regulatory region of copper-responsive miRNAs (Yamasaki et al 2009 ). Also the LONG HYPOCOTYL 5 (AtHY5) acting downstream of many families of photoreceptors, binds to the upstream region of several miRNAs (miR156d, miR172b, miR402, miR408, miR775, miR858, miR869, and miR1888) (Zhang et al 2011a ).…”
Section: Small Rna-mediated Signaling In Response To Abiotic Stressmentioning
confidence: 97%
See 1 more Smart Citation
“…A number of transcription factors including the master regulator PHOSPHATE RESPONSE 1 (PHR1), and several members of the MYB and WRKY families of transcription factors have been shown to regulate the transcriptional activation of lowphosphate responsive genes and their corresponding binding sites P1BS, MBS and the W-box, respectively, act as cis-acting elements that mediate Pi starvation-responsive expression. [15][16][17][18][19][20] A search for these cis-acting motifs in Pi-methDEGs showed that 39 of these genes contained P1BS motifs, that present the palindromic 8 base pair sequence (GNATATNC) where PHR1 binds to DNA as a dimer, 15 93 genes had W-box elements which are the cognate binding sites of WRKY transcription factors, which have been characterized as key regulators of several processes in plants, including some members of this family which are specifically involved in the response to low Pi conditions, 17,19,21,22 and 80 genes contained MYB transcription factors Binding sites (MBS) (Fig. 1B).…”
Section: Differential Methylation Nearby Pi Responsive Motif Sequencementioning
confidence: 99%